Knowledge Management and IT Governance in Higher Education: A Systematic Review and a Proposed Integration Framework - Domingas Soares; Dana Indra Sensuse; Ni Wayan Trisnawaty; Jacquline Waworundeng (Applied Information System and Management (AISM), 2026)
In the digital transformation era, higher education institutions (HEIs) in developing countries struggle to align information technology governance (ITG) with institutional goals because of fragmented knowledge and constrained resources. Knowledge management (KM) can address these challenges by supporting informed decisions, increasing transparency, and fostering organizational learning. This study conducts a systematic literature review (SLR) to examine how KM strategies enhance ITG in HEIs. Using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) procedures, we screened 3,361 records from IEEE Xplore, Scopus, ACM Digital Library, SpringerLink, Google Scholar, and ResearchGate; 20 studies met the inclusion criteria targeting the KM--ITG nexus in HEIs within developing countries (2020--2025). We applied thematic synthesis to answer two research questions (RQs): (RQ1) How do HEIs employ KM to strengthen ITG? (RQ2) Which strategies integrate KM with ITG? For RQ1, HEIs utilize KM to enhance IT decision-making, improve operational efficiency, accelerate digital transformation, and boost staff capacity. For RQ2, integration strategies comprise tailored governance models, digital platforms, communities of practice (CoPs), maturity assessment frameworks, and leadership-driven approaches. This review maps current KM--ITG practices, identifies enablers and barriers, and highlights the need for context-sensitive frameworks in the Global South. The findings synthesize strategies and practices that can guide the design of knowledge-based ITG models to support sustainable digital innovation in higher education.